Unexpected renal influence on isavuconazole trough concentrations: two case reports and literature review - Li, Hui; He, Xiaoshuang; Lu, Qiuya; Wang, Ling; Jiang, Jieling; Gao, Wenhui; Wang, Lining; Hu, Jiong; Fang, Jie; Bian, Xiaolan (Frontiers in Medicine, 2025)
Isavuconazole (ISA) is a first-line treatment for invasive aspergillosis, with routine therapeutic drug monitoring (TDM) typically deemed unnecessary. Although the drug label and prior studies suggest renal function does not affect ISA pharmacokinetics, our findings in two high-risk patients challenge this perspective, showing an inverse correlation between ISA trough concentrations and estimated glomerular filtration rate (eGFR). Trough concentrations exceeding the reported toxicity threshold were associated with adverse drug reactions (ADRs). Given the limited sample size, large-scale retrospective and prospective studies are urgently needed to confirm the impact of renal function on ISA and to develop individualized TDM strategies that optimize efficacy and minimize toxicity.